The Development of Student Mapping Tools Application (SMT) As an Early Detection System for Student-At-Risk (International Journal of Psychosocial Rehabilitation, 2020)
The development of the Student Mapping Tools (SMT) application was made with aims especially the teachers could map students who were suspected of having potential risk in their learning. The SMT application was made using a web-based PHP application programming language by using mapping database consist of psychological, physiological performance and potential academic of students. SMT displays the results of data extraction in the form of assessment results that can help schools and teachers in identifying and detecting students from the beginning in terms of (1) the psychological performance of students within psychological assessment results; (2) physiological performance through a series of health test results from medical laboratory; (3) potential academic obtained through academic test of students. The display of Psychological performance of students includes cognitive domain, learning attitudes and personality acquired by conducting a series of psychological tests. While the health performance is carried out by checking the blood, namely hematology, physical and fitness of students. The potential academic students obtained by conducting main academic test such as Mathematics, English language, Indonesia language and skill of reading Qur’an in Arabic language. Through SMT application can be a road map to identify, monitor learning activities, and interventions or instructional learning both for regular students or student at-risk.